Uma Abordagem Ontológica para Recomendação de Equipes Qualificadas em Projetos De Software - Pinheiro, Larissa Barbosa Leôncio (2014)
The object-oriented software componentization and development in the eighties aroused interested on developers towards the opportunities and advantages of software reuse, creating this same reuse in several stages of development, for instance, documentation, specification and modeling, increasing the search of better business opportunities, whether for reducing development costs or obtain produtivity gains. The development of these ideas led to the formulation of Software Product Lines model, which represents a shift in focus from the standardized paradigm of software development. Within this new paradigm, organizations that before addressed a project by project development software approach must now focus their efforts on creating and maintaining a line of software products which will be the basis for the production of a collection of products belonging to a "family". According to Clemente (2002), like all technological change, such a project should involve an assessment of the current situation of the company, an articulation of the desired state and the development of a plan to achieve this state. In the specific case of software product lines for being a model that directly interferes with the way of working of the company, extratechnological factors must be taken into account: adaptability of people, the type of training needed and preparing the client for new ways of working. The aim of this work is the creation of an Ontological approach to selection of distributed teams technically qualified for the implementation of software modules in a project of LPS, referring to the technical teams of the framework recommendations. This approach aims to provide decision support for project managers who aim to identify a set of qualifying teams for each module of a software project, taking into account the technical requirements of modules and technical skills in teams. This recommendation technical team was established by Santos (2010), using a fuzzy logic approach, structured in four stages. The first stage aims to produce a model description (generate an artifact) responsible for representing the technical requirements expected to implement each software module. The second step aims to generate a model of description responsible for representing the technical skills of the candidate teams to implement software modules. The third stage aims to define policies that will be responsible for selecting the qualified and/or able to implement software modules teams. Finally, the fourth step aims to cross the information obtained in previous steps and make the selection of the teams qualified for the implementation of the software modules. Thus, as a way out, for each software module recommendations are generated, which indicates team candidates who possess the most appropriate technical skills to implement software modules. Applying ontology to the problem of team recommendation is possible to represent the modules and their attributes in addition to expressing the relationships between the data collected, one can use axioms to deduce technically qualified teams. Team selection policies are offered with the intent of assisting the project manager in the selection of technically qualified teams for implementation of modules. In order to evaluate the ontological approach proposed, case studies are conducted, as well as a comparative study between the approach proposed in this paper and the fuzzy logic-based approach proposed by Santos (2010)